Interação Humano-Computador através de interfaces conversacionais: O caso de estudo do sistema NAVMETRO - Carlos José da Cruz Pinho (2016)
Currently there's a great concern to create compelling products that meet the needs of users and are easy to use.The literature proposes the use of several methodologies centered on the user during the interaction design project. However, this doesn't mean that they are implemented as proposed by the literature or are used by all professionals.Several authors report the most common reasons for not applying these methodologies, however, within the studied area, there are no studies that refer which methodologies are actually put into practice.This dissertation arises form an interest in the discrepancy between theory and practice, proposing to study project and evaluation methodologies in the interaction design project that are applied in a real context by small companies and teams located in the Porto metropolitan area.We used the snowball sampling technique and conducted in-person semi-structured interviews, from which we concluded that there is a concern with usability, even though most respondents do not perform usability tests. Wireframes, mockups and prototypes are the most used tools, and feedback from customers and users is considered very important for the iteration and development of products.